Operating Parameters and Environmental Indicators of Diesel Engines Fed with Crop-Based Fuels (Agricultural Engineering, 2021)
A comparative analysis of performance of Diesel engines fuelled by diesel oil, methyl ester of rapeseed oil and raw rapeseed oil was performed. The analysis of external characteristics of engines powered by various fuel types was accepted for an assessment. Engine performance rates were analysed while attention was paid to power courses, moment, unit fuel consumption and hour fuel consumption, exhaust fumes temperature and exhaust smoke. Operation effectiveness of engines was assessed when they were fed with various fuel types and optimal proportions of fuel mixtures were indicated. Environmental aspects of powering the engines with traditional fuels and crop-based fuels were analysed. The total CO2 emission in the entire process of manufacturing and combustion of fuels was accepted as a criterion. A simplified economic analysis was performed in the aspect of the underlying purpose of using crop-based fuels for propulsion of piston engines. Conclusions and recommendations that indicate directions of development concerning the analysed issue were prepared.